Kreativitas Linguistik dalam Iklan E-Commerce : Studi Perbandingan Wacana Persuasif antara Shopee dan Blibli (International Forum of Researchers and Lecturers, 2024)
This study aims to describe and analyze the discourse structure consisting of macro structure, supra structure, micro structure, and discourse contained in Shopee and Blibli online shopping advertisements. The object of the research is the transcript of online shopping advertisements from Shopee and Blibli. The data collection methods used were advertising observation and doing advertising transcripts so that the final data used was in the form of text. This data was then analyzed using a qualitative descriptive analysis model of Teun A Van Dijk's discourse analysis theory. From the data studied, the results of the study showed that (1) the macro structure or theme in the transcript of online shopping ads was seen in the entire content. The themes were big discounts, free shipping, cash back bonuses and discount vouchers. (2) The super structure consisted of (a) an introduction to the issue, (b) a series of arguments, (c) a statement of invitation, (d) a reaffirmation. (3) Microstructure consists of (a) background, (b) details, (c) meaning, (d) coherence marker, (e) stylistic, (f) rhetoric, (g) graphic use. (4) The discourse contained in the text was a persuasive discourse.